Community based reproductive health interventions for young married couples in resource-constrained settings: a systematic review. (December 2015) - Sarkar, Archana; Chandra-Mouli, Venkatraman; Jain, Kushal; Behera, Jagannath; Mishra, Surendra; Mehra, Sunil
Abstract Background Most pregnancies among adolescent girls and young women aged 15–24 years occur in low- and middle-income countries (LMICs), and do so within marriage. The mortality rates and pregnancy-related morbidities are significantly higher among the women of younger age group in many South Asian and Sub-Saharan African countries. This paper presents a review of the available evidence on the effectiveness of community-based health interventions to improve the reproductive health status of young married couples in LMICs. Method We carried out a systematic review of research studies and evaluation reports of different community-level initiatives in improving access to contraception, pregnancy care and safe abortion services by young married couples, where women were in the age-group of 15–24 years. Results Of the 14 projects, which met inclusion criteria, eight met the quality criteria and were included in the review (five from India, two from Nepal and one from Malawi). Our analysis shows that community-based interventions consisting of counseling of young married women, and their husbands, family and community members, as well as capacity building of health workers were some of the effective measures in increasing contraceptive use, delaying pregnancy and improving pregnancy care. Stratifying young women in line with their specific reproductive health needs (newly married woman, pregnant woman, mother of one/more children) was found to be a successful innovative strategy. None of these projects explicitly addressed improving access to safe abortion care. Conclusion Our review suggests that multi-layered community-based interventions, targeting young married women, their families and the health system can improve utilization of reproductive health services among young couples in resource-constrained settings. There is less focus on strategies to delay first pregnancy as compared to spacing among young women. Further, family and community level barriers in most of the project settings restricted its effective implementation. The paper emphasizes the need for further research to fill the knowledge gaps that exist about improving utilization of reproductive healthcare services, especially safe abortion care among young married women in LMICs.